Konsumsi Kurma pada Akhir Kehamilan Terhadap Percepatan Kala 1 Persalinan - Astari, Ruri Yuni; Dewi, Dzikri Yupita (Wellness And Healthy Magazine, 2019)
The first-stage is the beginning of labor that starts from the uterine contraction or known as "his" which is regular and continue to increase (both in the frequency and strength) until the cervix dilates to 10 cm (complete dilatation). The length of the first stage of labor for primigravidae is 12 hours while for multigravidae is 8 hours. This study aims to determine the effectiveness of the consumption of dates at the end of pregnancy on the acceleration of time period of the first stage of labor. The type of study used was a quasi-experimental with a static group comparison approach. The sampling technique used a purposive sampling approach. The samples in this study were 30 pregnant women with 37-38 weeks gestational age who were assigned in the control group and the experimental group (consuming dates) with 15 respondents, respectively). The study was conducted at Sumber Jaya Community Health Center in Majalengka District from April 1 to June 10, 2019. Univariate data analysis was conducted with central tendency distribution and bivariate analysis was conducted with paired t test. The results showed that the fastest progress of the first stage of labor that was seen from the duration until complete dilatation (10 cm) in group 1 (treatment) was 0 hour and in group 2 (control) was 1 hour, while the slowest progress in group 1 (treatment) was 3.5 hours and in group 2 (control) was 4 hours. The mean acceleration of the first stage of labor in term pregnant women who consumed dates was faster, namely 1.2 hours of 2.2 hours. Tcount value 3.347 and p value 0.002 which meant that the null hypothesis was rejected, so statistically the consumption of dates at the end of pregnancy was effective in accelerating the first stage of labor. Midwives or healthcare providers can provide alternative ways to accelerate the progress of the first stage of labor, namely by consuming dates before delivery as one way to facilitate labor.